SLEEP DURATION AND METABOLIC SYNDROME IN OBESE ADOLESCENTS - Nur Aisiyah Widjaja; Rendi Aji Prihaningtyas; Roedi Irawan; Meta Herdiana Hanindita (Media Gizi Indonesia, 2021)
Shorter sleep duration is a risk factor for obesity and metabolic syndrome. Previous studies conducted on diff erent races showed inconsistent results. The purpose of this study was to analyze the diff erences in sleep duration in obese adolescents who suff er from metabolic syndrome compared with obese adolescents who do not suff er from metabolic syndrome. A cross sectional study was carried out on 59 obese adolescents who visited the Pediatric Nutrition and Metabolic Disease Clinic in Dr. Soetomo General Academic Hospital, Surabaya. Subjects were selected using total sampling techniques who met the inclusion and exclusion criteria in August-November 2018. Anthropometry (weight, height and waist circumference), blood pressure, and blood tests (HDL cholesterol levels, triglycerides, and fasting blood glucose levels) were held to determine obesity according to CDC 2000 and metabolic syndrome according to International Diabetes Federation. The diff erence in sleep duration in obese adolescents suff ering from metabolic syndrome and without metabolic syndrome analyzed using Chi square test. A total of 27 subjects (45.8%) suff ered from metabolic syndrome. Most obese adolescents (57,6%) have suffi cient sleep duration (≥ 8 hours/day). There was no sleep duration diff erences in obese adolescents suff ering and not suff ering from metabolic syndrome (p> 0.05).